The framing of BBC Arabic online news on Trump's travel bans / Dania Yahya Hamed Ibrahim Ahamed Alshershaby - Dania Yahya, Hamed Ibrahim Ahamed Alshershaby (2019)
Translation studies have recently shifted their focus from equivalence (Bernaerts, De Bleeker and De Wilde, 2014) to notions of power, patronage (Lefevere, 1992, 2002; Haj Omar, 2016) and conflict identified under definite political agendas (Haj Omar, 2016). Also, narratives may intend to constitute reality which then urges translation into seemingly legitimatizing such attempts because even though translation transfers the real intentions and ideologies it is blamed as if it had created such narratives itself. This paper aims to examine the framing strategies and ideology shifts resulting from translating the January, March and June travel ban narratives through qualitative comparative analysis of the shifts in eight BBC Arabic (target text) narratives compared to their English (source text) BBC News equivalents, between January 2017 and June 2017, using Baker‟s (2006) narrative framing strategies based on Translation and conflict: A narrative account. Findings illustrate the simultaneous use of Baker‟s framing ambiguity, temporal and spatial framing, labeling, selective appropriation and participants repositioning to accentuate an ethnocentric narrative of reality. Further, findings propose the significance of original text (OT) in addition to source and target texts in understanding news narratives ideology shifts in Translation and Interpretation studies.